The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Physics of Biological Membranes 2018
DOI: 10.1007/978-3-030-00630-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Protein Pattern Formation

Abstract: Protein pattern formation is essential for the spatial organization of many intracellular processes like cell division, flagellum positioning, and chemotaxis. A prominent example of intracellular patterns are the oscillatory pole-to-pole oscillations of Min proteins in E. coli whose biological function is to ensure precise cell division. Cell polarization, a prerequisite for processes such as stem cell differentiation and cell polarity in yeast, is also mediated by a diffusion-reaction process. More generally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 96 publications
(152 reference statements)
0
35
0
Order By: Relevance
“…Intracellular pattern-forming systems are often based on reaction–diffusion networks ( 46 , 47 ). Their underlying nonlinearities render these networks sensitive to even small variations in system parameters, such as reaction rates and the (approximately constant) concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pattern-forming systems are often based on reaction–diffusion networks ( 46 , 47 ). Their underlying nonlinearities render these networks sensitive to even small variations in system parameters, such as reaction rates and the (approximately constant) concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Note that ‘chemical component’ does not refer to a protein species, but to the conformational state of a protein that determines its interactions with specific (conformations of) other proteins. Clearly, protein interaction networks include many conformational states—not just two [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems either use natural chemotaxis mechanisms to initiate spatial pattern formation of the bacterial density itself Tyson et al (1999), or instead use synthetic bacteria re-engineered to express additional quorum-sensing pathways that spatially coordinate patterns in gene expression (Basu et al 2005;Tabor et al 2009;Grant et al 2016). Other examples are synthetically reconstituted protein interaction systems with bulk-membrane coupling such as the Min system (Loose et al 2008;Kretschmer and Schwille 2016;Frey et al 2018), where molecular interactions (Denk et al 2018;Glock et al 2019), or in vitro system geometries (Wu et al 2016;Brauns et al 2020;, are modified to stimulate changes in the observed protein patterns. Examples of particular contemporary interest include the use of bacterial colonies as exemplars of synthetic multicellular communication and self-organization (Balagaddé et al 2008;Dalchau et al 2012;Payne et al 2013;Grant et al 2016;Karig et al 2018), for example using modified E. coli with engineered quorum-sensing signalling on the surface of an agar plate (Grant et al 2016;Payne et al 2013;Cao et al 2016Cao et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…A second class of model considers bulk-surface coupling, where one component is confined to the boundary of the main bulk domain, and reactants flow between the two regions, such as in the case of proteins diffusing in the cytoplasm and binding on the cell membrane (Rätz and Röger 2014;Madzvamuse et al 2015;Spill et al 2016;Cusseddu et al 2018;Paquin-Lefebvre et al 2018;Frey et al 2018). There is substantial recent interest in such models, from very theoretical results on existence and fast reaction-limiting behavior (Rätz 2015;Anguige and Röger 2017;Hausberg and Röger 2018), to spike dynamics (Gomez et al 2018) and a myriad of applications to understanding cell polarity (Thalmeier et al 2016;Kretschmer and Schwille 2016;Geßele et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation